2021
DOI: 10.1007/s00339-021-05194-1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and desorption behavior of titanium-decorated polycrystalline graphene toward hydrogen storage: a molecular dynamics study

Abstract: The hydrogen adsorption and desorption capacity of polycrystalline graphene sheets (PGs) with and without titanium (Ti) decoration is investigated using molecular dynamics simulations. Interatomic interactions of PGs are modeled using Tersoff potential, and the remainder of interactions are calculated via Lennard-Jones potential. The effect of grain size and Ti concentration on the mechanical properties and hydrogen adsorption capacity of PGs is studied. The presence of grain boundaries in PGs reduces their me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In the case of 1% Ti-decorated polycrystalline graphene, the HSC reaches 3.2 wt% at 300 K and 9.9 wt% at 77 K, both under a 100 bar pressure. 183 3.2.2.2. Titanium-decorated N/B-doped graphene for hydrogen storage.…”
Section: Transition Metal-doped Graphene For Hydrogen Storagementioning
confidence: 99%
“…In the case of 1% Ti-decorated polycrystalline graphene, the HSC reaches 3.2 wt% at 300 K and 9.9 wt% at 77 K, both under a 100 bar pressure. 183 3.2.2.2. Titanium-decorated N/B-doped graphene for hydrogen storage.…”
Section: Transition Metal-doped Graphene For Hydrogen Storagementioning
confidence: 99%
“…This metal is adsorbed in graphene with a high energy (−1.98 eV) 22 high capacity for storing hydrogen (9.9 wt % at 77 K). 23 However, cluster formation has limited its use in the hydrogen storage industry. In 2018, Yuan et al showed that the adsorption energy of the Ti atom on the graphene sheet was −3.65 eV.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, due to the small size and gaseous nature of H 2 , efficient storage of H 2 is the main bottleneck for its practical applications. Recently, H 2 storage on surfaces of nanostructures such as graphene was suggested by adsorption of H 2 on their surfaces, which improves the quality by overcoming a high operating temperature and slow kinetics. It has been found that transition metal atoms are decorated on carbon nanomaterials to store H 2 on a molecular form of H 2 because H 2 can be adsorbed on the metal atoms through the hybridization of metal “d” orbitals with H 2 “σ” and “σ*” orbitals, which is called Kubas-type H 2 storage materials. …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Kubas-type H 2 storage materials have received much attention because they can be used for room-temperature H 2 storage, since the adsorption energy of H 2 fulfills the condition (∼0.2 to 0.4 eV) of room-temperature H 2 storage. However, it has been found that the capability of H 2 storage at room temperature is diminished because metal clustering is in energy favorable due to their large cohesive energy (∼4 eV) . On the other hand, Kubas-type H 2 storage materials, multilayer Ti 2 CT x , have been synthesized and the performance of H 2 storage capability has been demonstrated .…”
Section: Introductionmentioning
confidence: 99%